PELATIHAN PERTOLONGAN PERTAMA PADA BAYI HENTI NAFAS DI POSYANDU KELURAHAN MAMBURUNGAN TIMUR - Ika Yulianti; Tanti Tri Lesytary; Yuni Retnowati; Nenden Imas Andini; Elfanda Sholihah Uzakki (Jurnal Inovasi dan Terapan Pengabdian Masyarakat, 2022)
Babies are very vulnerable to emergencies such as choking which results in stopping breathing. This happens because of the process of adjusting the function of the body's organs from life intrauterine to extrauterine. So babies need optimal supervision from their families, especially mothers. But unfortunately there are still many mothers who do not know about the first aid for choking babies until they stop breathing. This training is held to increase the knowledge and skills of mothers in performing first aid for stopping breathing for babies when it occurs at home. This Training is carried out at the Posyandu, Kelurahan Mamburungan Timur, Kota Tarakan.